Purulent pleurisy in children - Mouad Fatima Zahra; Elmoussaoui S; Elfakiri K; Rada N; Draiss G; Soraa N; Bouskraoui M (Open Journal of Bacteriology - Peertechz Publications, 2020)
Introduction: The incidence of purulent pleurisy is on the rise in several series in the literature. It is a significant cause of morbidity in pediatrics. The main objective of our study is to analyze the epidemiological characteristics and the prognosis of purulent pleurisy of the child.  Material and methods: We conducted an 11-year retrospective study (2008-2019), including 74 children with documented pleurisy, who were hospitalized in the Department of Pediatrics A of the Mohammed VI University Medical Center in Marrakesh. Results: Purulent pleurisy accounts for 0.5% of pathologies in children. The average age was 4.5 years, with a male predominance (70% of boys). The average time before consultation was 15 days. Respiratory symptoms were cough (82%), chest pain (41%), and dyspnea (29%). Clinical examination revealed fluid effusion syndrome (97%). On chest X-ray, the effusion was often unilateral (95%), of average or large abundance (48% and 46% respectively). Thoracocentesis for diagnostic and therapeutic purposes was performed in 84% of cases. Surgery for complicated pleurisy or drainage failure was reported in 20% of patients. Conclusions: Pneumococcus and Staphylococcus aureus remain the main germs of the child's purulent pleurisy. Thanks to the exclusive use of chest drainage associated with antibiotic therapy, the prognosis of our patients is satisfactory.